Innovations in Biomedical Engineering (Advances in Intelligent Systems and Computing,, 2018)
This book presents the proceedings of the "Innovations in Biomedical Engineering IBE'2017" Conference held in Zabrze, Poland from October 19 to 20, 2017, and discusses recent research on innovations in biomedical engineering. The book covers a broad range of subjects related to biomedical engineering innovations. Divided into four parts, it presents state-of-the-art advances in: Engineering of biomaterials, Modelling and simulations in biomechanics, Informatics in medicine, and Signal analysis. By doing so, it helps bridge the gap between technological and methodological engineering achievements on the one hand and clinical requirements in the three major areas diagnosis, therapy and rehabilitation on the other.